MORPHOMETRIC INVESTIGATION OF INFRAORBITAL FORAMEN IN HUMAN DRY SKULLS AND IT’S CLINICAL IMPLICATIONS, PATNA: A CROSS-SECTIONAL STUDY. - Vivekanand; Kumari Rashmi; Birendra Kumar Sinha (Student's Journal of Health Research Africa, 2024)
Background The infraorbital foramen (IOF) is a key anatomical landmark on the maxillary bone, crucial for the exit of the infraorbital nerve and vessels. Precise knowledge of its morphology is vital for maxillofacial surgeries, anesthesia, and dental procedures to prevent complications such as nerve damage. This study provides detailed morphometric data on the infraorbital foramen in human dry skulls of the Indian population. Methods A cross-sectional investigation was carried out on sixty dry human skulls. The measurements included the oblique distance, the transverse diameter, and the sagittal distance. The shape, orientation, and existence of accessory infraorbital foramina on both sides of the skulls was noted. An analysis of the data was done using SPSS Version-23. Results The mean sagittal distance was 6.8 mm, transverse diameter was 14.3 mm, oblique distance was 22.5 mm, vertical diameter was 3.5 mm, and transverse diameter of the IOF was 4.2 mm. No significant variations were found between the right and left sides. The IOF was predominantly oval-shaped (75%) with a downward and medial orientation (83.3%). Accessory infraorbital foramina were present in 20% of the skulls, varying from 1 to 3 per skull. Conclusion The study provides comprehensive morphometric data on the IOF in the Indian population, indicating no significant bilateral differences. The predominance of oval-shaped foramina and the presence of accessory foramina have important clinical implications for surgical precision and patient safety. Recommendations Future studies should utilize advanced imaging techniques to validate these findings in living subjects. Surgeons should consider these anatomical variations to minimize complications during maxillofacial and dental procedures.